STRATEGI PROMOSI, CITRA MEREK, DAN MINAT BELI PADA DISTRO BANDUNG OBLONG - Suparwo, Adi; Supriadi, Aldi Anggara; Sukajie, Bambang (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2024)
This research aims to determine the influence of promotional strategies and brand image on consumer buying interest in the Bandung Oblong (Baong) distro. This research uses descriptive and verification research methods with a quantitative approach. The objects of this research were Baong distro consumers with a sample size of 96 people. The sampling technique used in this research is a nonprobability sampling method with a purposive sampling technique. Statistical analysis of the data used in this research is multiple linear regression analysis and hypothesis testing using t and F tests using IBM SPSS statistics 27. The results of the research show that partially the promotional strategy variable has a significant effect on consumer buying interest in Baong distros, and partially the brand image variable does not have a significant effect on Buying interest in the Baong distro, as well as simultaneously promotional strategies and brand image have a significant effect on consumer buying interest in the Baong distro, with a coefficient of determination (R Square) obtained a value of 0.617 which shows that 61.7% of buying interest can be explained by the promotional strategy and brand image while the remaining 38.3% of purchasing interest is influenced by other variables not examined in this research”